2004
DOI: 10.3168/jds.s0022-0302(04)70038-7
|View full text |Cite
|
Sign up to set email alerts
|

Destruction of Mycobacterium paratuberculosis, Salmonella spp., and Mycoplasma spp. in Raw Milk by a Commercial On-Farm High-Temperature, Short-Time Pasteurizer

Abstract: The 2002 NAHM's Dairy Survey indicated that 87.2% of dairy farms in the United States feed waste milk to their neonatal calves. Although cost-effective, this practice can lead to increased calf morbidity and mortality due to ingestion of pathogenic agents. In an effort to reduce the risk of infection, dairy producers are implementing on-farm pasteurization of the waste milk as a control procedure before feeding the milk to calves. In the present study, the efficacy of a commercial high-temperature, short-time … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(79 citation statements)
references
References 12 publications
1
75
0
3
Order By: Relevance
“…Green et al (2003), using HTST (high-temperature short-time, 72°C for 15 s) pasteurisation of colostrum, reported an average 28.4% loss of native IgG, and that all samples congealed into a thick, pudding-like consistency during or immediately after pasteurisation. These results are in agreement with those of Stabel et al (2004), who reported a 25% reduction in native IgG concentration and gelling of the colostrum after HTST pasteurisation.…”
Section: Somatic Cell Countsupporting
confidence: 83%
“…Green et al (2003), using HTST (high-temperature short-time, 72°C for 15 s) pasteurisation of colostrum, reported an average 28.4% loss of native IgG, and that all samples congealed into a thick, pudding-like consistency during or immediately after pasteurisation. These results are in agreement with those of Stabel et al (2004), who reported a 25% reduction in native IgG concentration and gelling of the colostrum after HTST pasteurisation.…”
Section: Somatic Cell Countsupporting
confidence: 83%
“…Colostrum can be contaminated by microorganisms, which can reduce animal performance as well as increase morbidity and mortality rates (Godden, 2008;Stabel et al, 2004). These pathogens may originate from the mammary gland or contaminate the colostrum during collection, manipulation, and storage processes (Stewart et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Algunos de los patógenos que pueden estar presentes en el calostro, ya sea provenientes de la glándula mamaria o de la contaminación en el manejo del mismo y que pueden ser transmitidos a las terneras incluyen: Mycobacterium avium spp. Paratuberculosis, Salmonella spp., Micoplasma spp., Listeria monocytogens Campylobacter spp., Mycobacterium bovis y Escherichia coli (Dominguez 1997;Stabel 2001;Stabel 2004;Stewart 2005;Godden et al 2006). Estos agentes infecciosos pueden ocasionar enfermedades como la enteritis y septicemia.…”
Section: Pasteurización Del Calostrounclassified